Correlation between markers of peripheral nerve function and structure in type 1 diabetes. Issue 7 (3rd July 2018) - Borire, Adeniyi A.; Issar, Tushar; Kwai, Natalie C.; Visser, Leo H.; Simon, Neil G.; Poynten, Ann M.; Kiernan, Matthew C.; Krishnan, Arun V.
Abstract: Background: Clinical and experimental studies in patients with type 1 and type 2 diabetes have demonstrated changes in ion channel function and nerve structure. In this study, we investigated the relationship between axonal dysfunction and morphological change in diabetic polyneuropathy by using neuromuscular ultrasound and nerve excitability techniques. We also explored possible differences in this relationship between type 1 and type 2 diabetes. Methods: Nerve ultrasound and corresponding motor excitability studies were undertaken in 110 diabetes patients (50 type 1; 60 type 2) and 60 age‐matched controls (30 for each group). Neuropathy severity was assessed by using total neuropathy score. Median and tibial nerve cross‐sectional areas were measured at nonentrapment sites by using high‐resolution linear probe. Results: Median and tibial nerve cross‐sectional areas were significantly higher in diabetes patients compared with controls: type 1 (median = 7.6 ± 0.2 mm 2 vs 6.3 ± 0.1 mm 2 ; tibial = 14.5 ± 0.7 mm 2 vs 10.8 ± 0.3 mm 2, P  < .05) and type 2 (median = 9.1 ± 0.3 mm 2 vs 7.2 ± 0.1 mm 2 ; tibial = 18.5 ± 1.0 mm 2 vs 12.8 ± 0.5 mm 2, P  < .05). In the type 1 cohort, significant correlations were found between nerve cross‐sectional area and excitability parameters including resting current‐threshold slope (median: r  = 0.523, P  < .0001; tibial: r  = −0.571, P  = .004) and depolarizing threshold electrotonus at 90 to 100 ms (median: 0.424, P  < .01; tibial: r  = 0.435, P  = .030). In contrast, there was no relationship between excitability values and nerve cross‐sectional area in the type 2 cohort. Conclusions: This study has identified correlation between markers of axonal membrane function and structural abnormalities in peripheral nerves of type 1 diabetes patients. The differential relationship in nerve function and structure between type 1 and type 2 diabetes provides clinical evidence that different pathophysiological mechanisms underlie the development of neuropathy in these patient groups.